A 3-day course of 1 mg/kg versus 2 mg/kg bodyweight prednisolone for 1- to 5-year-old children with acute moderate exacerbation of asthma: a randomized double-blind noninferiority trial. Issue 4 (28th July 2020) - Buddala, Pavan Kumar; Chandrasekaran, Venkatesh; Harichandrakumar, K T
Abstract: Background: Even though the guidelines on the management of preschool asthma recommend early use of corticosteroids for acute moderate-to-severe exacerbations, considerable variation exists with regard to type and dose of steroids. Objectives: To compare the clinical outcomes and side effect profile between 1 mg/kg/day and 2 mg/kg/day of oral prednisolone when administered for 3 days in preschool children with acute moderate asthma exacerbations. Study Design and Setting: Randomized double-blind noninferiority trial was done in the paediatric emergency of a teaching hospital. Patients, Interventions, and Outcomes: A total of 128 children aged 1 to 5 years who presented to the paediatric emergency with acute moderate exacerbation of asthma were enrolled. They were randomized into two groups. One group received 1 mg/kg/day and the other 2 mg/kg/day of oral prednisolone for 3 days. Severity of asthma exacerbation was measured by Pediatric Respiratory Assessment Measure (PRAM) score. The PRAM scores, wheeze recurrence, and side effect profile were compared and analyzed between the two groups. Results: The difference in the PRAM scores at 1, 2, 3, and 4 hours after intervention between the two groups was statistically insignificant. Need for escalation of therapy, salbutamol nebulization, time for resolution of symptoms, and recurrence of wheeze were similar between the two groups. Vomiting was significantly less frequent in low-dose group with a relative risk of 0.19 to 0.99 compared to high-dose prednisolone. Conclusion: Prednisolone at a dose of 1 mg/kg/day was not inferior to 2 mg/kg/day in terms of clinical improvement and recurrence of wheeze within 1 week and has less frequent vomiting compared to higher dose.